Effect of Chitosan on the Corrosion Protection of Aluminum in H2SO4 medium - Arwati, I Gusti Ayu (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2018)
Metal aluminium alloy 5052 is a metal that has a lightweight nature of its utilization is very wide. In addition to light also has other advantages such as a good introduction to heat. But the weakness of this material is easily corrosive in the acid environment. To reduce corrosion rate is generally used inorganic inhibitors such as cremate, but these inhibitors are toxic and can contaminate the environment. This study aims to reduce the corrosion rate of aluminium alloys by using non-toxic and environmentally friendly green chitosan inhibitors. The method used for coating on aluminium alloys by coating the metal by electrophoresis deposition (EPD). For corrosion rate testing using weight loss method in 0.5M H2SO4 environment and surface analysis using scanning electron microscope (SEM). The results showed that for 7 days the immersion of Al5052 alloyed uncoated a corrosion rate of 3.571 x 10 -5g / Cm2 days but, after coated with chitosan inhibitor the corrosion rate decreased by 1.73 10 -5 g / Cm 2 days.